2014
DOI: 10.1007/s00792-014-0681-6
|View full text |Cite
|
Sign up to set email alerts
|

The Santa Pola saltern as a model for studying the microbiota of hypersaline environments

Abstract: Multi-pond salterns constitute an excellent model for the study of the microbial diversity and ecology of hypersaline environments, showing a wide range of salt concentrations, from seawater to salt saturation. Accumulated studies on the Santa Pola (Alicante, Spain) multi-pond solar saltern during the last 35 years include culture-dependent and culture-independent molecular methods and metagenomics more recently. These approaches have permitted to determine in depth the microbial diversity of the ponds with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
85
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 81 publications
1
85
0
Order By: Relevance
“…They have a higher DO and proportion of organic matter and total phosphorous as well as a lower conductivity than mat samples. It is known that hypersaline environments have a low diversity, where halophilic microorganisms are able to survive to these extreme conditions because they have specific strategies to balance the osmotic pressure [32,33]. Moreover, it has been seen that these systems usually have very low organic carbon and nitrogen content [8,25,30,34].…”
Section: Discussionmentioning
confidence: 99%
“…They have a higher DO and proportion of organic matter and total phosphorous as well as a lower conductivity than mat samples. It is known that hypersaline environments have a low diversity, where halophilic microorganisms are able to survive to these extreme conditions because they have specific strategies to balance the osmotic pressure [32,33]. Moreover, it has been seen that these systems usually have very low organic carbon and nitrogen content [8,25,30,34].…”
Section: Discussionmentioning
confidence: 99%
“…the best-studied hypersaline system with respect to its microbiology with nearly continuous study for >35 years [Reviewed in [17]]. The first metagenomic studies on this saltern were focused on the saturated NaCl ponds and showed that the community was dominated by Haloquadratum walsbyi, which demonstrated tremendous genome plasticity and high gene content variability among close relatives [18,19], features later observed in other haloarchaeal species [20,21] and in Salinibacter ruber [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades several studies have been performed on diversity in coastal solar salterns in different geographic areas including Tunisia, Israel, Australia, Mexico, and India [2, 48]. In Europe, hypersaline microbiota has been intensively investigated in coastal salterns located in Spain [911] and Croatia [12]. These studies have revealed community heterogeneity between sites that have repeatedly been reported over the years [2, 6, 12, 13].…”
Section: Introductionmentioning
confidence: 99%